Geotechnical engineering for infrastructure and development : proceedings of the XVI European Conference on Soil Mechanics and Geotechnical Engineering - Winter, M. G.; Smith, D. M.; Eldred, P. J. L.; Toll, D. G. (Thomas Telford, 2015)
The XVI European Conference on Soil Mechanics and Geotechnical Engineering was held in Edinburgh, the capital of Scotland in September 2015. It was hosted by the British Geotechnical Association (BGA), the United Kingdom (UK) member society of the International Society for Soil Mechanics and Geotechnical Engineering (ISSMGE). This conference and the written proceedings that this paper introduces showcased geotechnical engineering in the UK, the rest of Europe and, indeed, many other parts of the World.